Did Morality First Evolve in Homo erectus? - Rappaport, Margaret Boone; Corbally SJ, Christopher (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2016)
With findings from cognitive science, neuroscience, information science, and paleoanthropology, an anthropologist and astronomer-priest team take a new look at the nature of morality, and suggest parameters that are often very different from the philosophical and theological literatures. They see morality as a biologically-based arbitration mechanism that works along a timeline with a valence of good to bad. It is rational, purposeful, social, and affected by emotion but not dominated by it. The authors examine the age and sex structure, family roles, environment, cognition, and lifeway of Homo erectus, an early hominin who arose 1.9 million years ago, and propose that he had a rudimentary moral system that his biology and culture enabled – but only after he learned to control fire. Hearths gave rise to an intense, social, emotional, experiential context where belief systems could be learned by youth before they achieved adult cognition.